Contemporary therapeutic approaches to atopic dermatitis: role of phototherapy and searching for new possibilities - I. V. Kosheleva; A. R. Khasanova (Лечащий Врач, 2021)
The report presents the results of the IL4 and IL10 serum levels investigation in patients with atopic dermatitis during the exacerbation of the disease and after phototherapy, as well as in comparison with healthy donors. The obtained results showed higher concentrations of IL10 in patients with atopic dermatitis during exacerbation and decrease of its level after phototherapy.